Human Resources Management Function, Technology Capabilities and Quality of Work Life Towards Competitive Advantage - Zahara Tussoleha Rony; Dian Yulianti (Jurnal Ilmu Manajemen Advantage, 2023)
This study aims to analyze the effect of human resources management function, technology capabilities to competitive advantage through quality of worklife as an intervening variable. Data were analyzed using statistical software LISREL 8.7. This result of this research are the effect of human resources management function to quality of worklife is significant so the hypothesis is accepted;the effect technology capabilities to quality of worklife is not significant so the hypothesis is rejected; the effect of human resources management function to competitive advantage is not significant so the hypothesis is rejected; the effect technology capabilities to competitive advantage is not significant so the hypothesis is rejected; the effect quality of worklife to co competitive advantage is not significant so the hypothesis is rejected. This research is only used in a limited and homogeneous sample, this research can give consideration to hospital leaders in making decisions regarding the program that will be used to provide solutions to problems that occur.